Strategi Pengembangan Desa Wisata dalam Lomba Spot Selfie Kelurahan Jatirejo Kecamatan Gunungpati - Dimas Maulana Saputra; Muhammad Alwi Waffa; Muhammad Auliya Elhakim; Lailatul Husna; Ngabdilah Fauziah; Chusnul Adib Achmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The development of tourist villages has become a global trend driven by cultural and environmental preservation, as well as its potential to increase local community income. The purpose of this research is to analyze the development strategy of Jatirejo Village, Gunungpati District, through the Spot Selfie Competition, which leverages the village's potential to attract tourists, especially the younger generation. This competition is not merely a selfie spot contest but also an effective tourism promotion tool that can spark community creativity in creating attractive selfie spots. The results of the study show a positive impact on increasing tourist numbers, local income, and the preservation of culture and the environment. Moreover, this spot selfie competition introduces innovation in the sustainable management of tourist villages. This research is expected to contribute to effective and sustainable tourist village development policies in Indonesia